Effectiveness of Using Telemedicine in Type 1 Diabetes Patients During the COVID-19 Pandemic - Grara Vema Tuzauna; Helen Andriani (Health Notions, 2021)
The COVID-19 pandemic has had a major impact on people with comorbid conditions. Routine examination of patients with chronic diseases such as diabetes has become a challenge during the COVID-19 pandemic. Telemedicine is an effective way to provide health services to diabetic patients, so that this motivates researchers to develop this study aims to explore accurate evidence regarding the effect or effectiveness of using telemedicine in type 1 diabetes patients in the COVID-19 era. This study used a systematic review with the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) method without meta-analysis. The articles used in this study were articles in the Scopus, ProQuest, and ScienceDirect databases; search using the keywords “Effectiveness AND Telemedicine OR Telehealth AND Diabetes Type 1 AND COVID-19”. The use of the telemedicine method for type 1 diabetes patients during the COVID-19 pandemic allows the provision of consultations and health checks through online communication media. Technological advances and the development of new devices will increase the ease between patients and health workers in exchanging information, and the use of telemedicine is the right choice during a pandemic to limit mobility and interaction to health facilities. Keywords: COVID-19; diabetes; telemedicine; telehealth